If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 2x + 2x = 46 Combine like terms: 2x + 2x = 4x 10 + 4x = 46 Solving 10 + 4x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 4x = 46 + -10 Combine like terms: 10 + -10 = 0 0 + 4x = 46 + -10 4x = 46 + -10 Combine like terms: 46 + -10 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 8-4x-4x=-48 | | 2x+y-6=6x+3y-12 | | 2b+8=54 | | 9x-9=6x+18 | | 4x^3(7x^3-16)+7=0 | | 5[2(3x+22)-11]+4=29 | | 4x-5=7x+25 | | y=(x^2+x-5)*sinx | | 2.56=2.6c | | 3a+b=110 | | 2p=2p+6-3 | | 4m-8-1m+-3=m-1 | | x/10-1=-2 | | 9k+33=-2k | | x/8-6=6 | | 6e^3x+4=16 | | 9m^2+1=28 | | -225/v=15 | | -5(6+z)=20 | | 2.4e+9=x | | 5x+3=-17+3x | | 28x^6-64x^3+7=0 | | 4x+16=x-2x | | 3^-xd/dx | | (16x-6)=90 | | (X^3-8x^4)/2x^2 | | 1/3x-16=11 | | y=7x^5+2x^3+2x^2+5x+3 | | 3(x-2)-8=6(x-2)+16 | | x+(x+1)+(x+3)=3x+7 | | 3a-(2a+3)+5(2a+1)= | | x+2y-z=-7whatisx |